Accessibility and public information of medical students’ Facebook profiles in a Peruvian medical school: A call to adapt e-professionalism guidelines in the Latin American context - Aragón-Ayala, Carlos Jesús; Cornejo-Estrada, Aldo Patricio; Rodriguez-Carrillo, Henry; Quispe-Juli, Cender Udai (Revista Cubana de Información en Ciencias de la Salud, 2023)
The use of Facebook poses new challenges for adoption of e-professionalism. In this study, we describe the accessibility of Facebook profiles in medical students from a Peruvian university, the disclosure of personal and professional information, and its association with sex and year of study. Through a systematic search on Facebook, the profiles of medical students from the 2nd to the 7th year were located using fictitious profiles. The presence of different types of information in accessible profiles was evaluated. The proportion of the disclosed content was calculated. The data were compared according to year of study and sex. Approximately 80% of the students (488/611) had public access profiles, although these were not significantly different according to year of study (p = 0.098) and gender (p = 0.912). Proportion of disclosed content was greater in higher years: 2nd and 3rd (p = 0.022), 2nd and 6th (p < 0.001), and 2nd and 7th (p = 0.002) and in men (33.25 ± 12.47) compared to women (30.38 ± 11.95) (p = 0.01). Photos (p = 0.009) and links to other social networking sites (p = 0.036) were more commonly visible in women’s profiles, while showing the university (p = 0.017), medical school (p = 0.043) and sexual orientation (p = 0.001) was more common amongst men. Most of the Facebook profiles of medical students were accessible, the disclosed content was greater in senior and male students. It is necessary to create and implement guidelines on e-professionalism in Latin America.